Rosenthal Relief Reihe : Ars Porcellana. (Köln : Kunstverein, 1968)
Avramidis, Joannis ; Cimiotti, Emil ; Croissant, Michael ; Fontana, Lucio ; Grieshaber, HZP ; Hadzi, Dimitri ; Hajdu, Etienne ; Hajek, O.H. ; Hartung, Karl ; Heiliger, Bernhard ; Koenig, Fritz ; Loth, Wilhelm ; Mavignier, Almir ; Moore, Henry ; Nele, E.R. ; Pasmore, Victor ; Peters, Herbert
Rosenthal Relief Reihe, Kunstverein, Köln, 1968
kunstcatalogus